2012
DOI: 10.1007/s10591-011-9170-6
|View full text |Cite
|
Sign up to set email alerts
|

Nonverbal Behavioral Indicators of Negative Affect in Couple Interaction

Abstract: Affect has been identified across numerous research studies to be a vital element in understanding couple relationship processes. Affect has been shown to distinguish between satisfied and dissatisfied couples and to be important in understanding processes leading to relationship dissolution. However, research has not yet uncovered nonverbal indicators that a couple is experiencing negative affect compared to other affective states. In this study we sought to identify specific nonverbal behaviors associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Specifically, we found that there was a tendency for the relationship between state NA and state analytical decision making to be negative, such that low state NA seemed to encourage state analytical decision making. To further iterate, during one exemplar surgical procedure, the mood in the room was light, and the clinicians made friendly small talk among each other and with the patient—indicating low state NA (Patterson et al, 2012). The nurse was monitoring vitals and taking detailed notes throughout the procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we found that there was a tendency for the relationship between state NA and state analytical decision making to be negative, such that low state NA seemed to encourage state analytical decision making. To further iterate, during one exemplar surgical procedure, the mood in the room was light, and the clinicians made friendly small talk among each other and with the patient—indicating low state NA (Patterson et al, 2012). The nurse was monitoring vitals and taking detailed notes throughout the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Behaviors indicative of state NA (including verbal cues; language, tone of voice) were coded, using previous work on observing NA as a guide (i.e., Butler & Geis, 1990; Patterson, Gardner, Burr, Hubler, & Roberts, 2012; see Table 6). Because situations varied widely on the appropriateness of display of NA and the use of these nonverbal indicators, each situation was analyzed based on context.…”
Section: Methodsmentioning
confidence: 99%
“…The above studies highlight some of the unique stressors that influence the relational dynamics in police officers and their spouses. The regulation of negative and positive affect is critical in coping with stress (Moskowitz 2010 ), and if left unattended, Patterson et al ( 2012 ) suggests that this can lead to marital dissatisfaction. Therefore, it is important to not only understand how stress affects the emotional dynamics of the couple relationship, but also how their mechanisms of coping minimize or exacerbate these effects.…”
Section: Challenges Specific To Law Enforcement Couplesmentioning
confidence: 99%
“…Another study found that the imitation of a personal choreography, movement synchronization, and collaboration in resolving incidents of non-synchronization of movement resulted in higher marital satisfaction, more secure attachment, and higher empathy in the relationship (Pietrzak et al, 2017 ). Furthermore, couples reported experiences of movement with their hands (Wagner and Hurst, 2018 ), being led in space by their partner (Polo, 2010 ), mirroring and imitating movement (DeBoer, 2006 ; Patterson et al, 2012 ; Lacson, 2020 ), raised awareness of emotional content from the couples' daily lives, and the ability to understand the emotional needs of the partner. The interventions in the various studies range from 8 h (Kim et al, 2013 ) of practice to 12 h (Hawkes, 2003 ; Pietrzak et al, 2017 ) as similarly described above in DMT interventions with adults diagnosed with ASD.…”
Section: Dmt For Couplesmentioning
confidence: 99%